Investigating Students’ Experiences and Preferences on Tools and Activities in Emergency Remote Learning Amidst Covid-19 Pandemic - Ratnawati Ratnawati; Indah Nurhasanah (Al-Lisan: Jurnal Bahasa, 2021)
The study investigates students’ recognition, students’ preferences, and students’ reasons for learning platforms, tools, and activities in the Emergency Remote Teaching (ERT) context. The intrinsic case study is used in the present study, which fully expected the quality of improvement and case evaluation can be carried out. The purposive sampling was used with 25 students of third-year class at a private university in West Java at English language education study program. In collecting the data, mixed questionnaire, participant classroom observation, and online semi-structured interview were distributed and conducted during the meetings, then analysed descriptively and thematically. The research findings point out that students positively responded to utilising Google Classroom for written synchronous and Zoom Cloud Meeting for virtual synchronous. To sum up, both platforms are recommended to be utilized in the online atmosphere for ERT. Further actions call for other researchers and educators to utilize them in classroom activities with similar backgrounds and problems. Besides, it is recommended for other researchers to conduct further studies related to the present field.